2018
DOI: 10.1111/1753-0407.12643
|View full text |Cite
|
Sign up to set email alerts
|

Identification of stress‐related microRNA biomarkers in type 2 diabetes mellitus: A systematic review and meta‐analysis

Abstract: The present meta-analysis revealed that 16 stress-related miRNAs were significantly dysregulated in T2DM. MiR-148b, miR-223, miR-130a, miR-19a, miR-26b and miR-27b were selected as potential circulating biomarkers of T2DM. In addition, miR-146a and miR-21 were identified as potential tissue biomarkers of T2DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 90 publications
2
48
0
Order By: Relevance
“…In relation to miR‐29b and type 2 diabetes, our results are in accordance with a recent meta‐analysis that identified stress‐related miRNA biomarkers in different tissue types and species. The authors found that miR‐29b was not dysregulated in type 2 diabetes in the subgroup analyses of miRNAs in circulating blood and in human profiling studies . However, these findings contrast with studies that reported either higher circulating levels of miR‐29 in subjects with prediabetes and type 2 diabetes or lower miR‐29b levels in those with prediabetes and who developed type 2 diabetes in the prospective population‐based Bruneck study .…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…In relation to miR‐29b and type 2 diabetes, our results are in accordance with a recent meta‐analysis that identified stress‐related miRNA biomarkers in different tissue types and species. The authors found that miR‐29b was not dysregulated in type 2 diabetes in the subgroup analyses of miRNAs in circulating blood and in human profiling studies . However, these findings contrast with studies that reported either higher circulating levels of miR‐29 in subjects with prediabetes and type 2 diabetes or lower miR‐29b levels in those with prediabetes and who developed type 2 diabetes in the prospective population‐based Bruneck study .…”
Section: Discussionmentioning
confidence: 77%
“…Despite the limitations, our findings support the perspective of using circulating miRNA levels as biomarkers of prognosis in type 2 diabetes and highlight the need for further research on them. As already recognized by other authors, although in vitro and animal studies are essential to elucidate the mechanistic effects, the same miRNAs may be differentially expressed between humans and animals, and even in different cell and tissue types, including vitreous, retinal endothelial cell and whole retina …”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations